(untitled) (Al-Academy, 2022)
Water represents as a basic intellectual material in the myths of creation and the start of formation, Thus, water has turned into an intellectual material in literary mythological texts in addition to its function in sculptural Mesopotamian sculpture. The research is in three sections: the first section deals with Myth, its concept, peculiarities and types, the second section is about mythological literature, the third section is about the idea of ​​water and mythical literature. The question research question here is that does the idea of water have any impact on mythological literature? And Does it link to sculptural products? The importance of the research is that it shows the human imagination and its relationship to functioning water as a literary, mythological and formational element to discover its impact between mythological literature and Mesopotamian sculptures, and results summarizing the idea of water, and its meanings between mythological literature and Mesopotamian sculptures